A study on how layout, motivation, and ergonomics can affect job productivity at Pejabat MARA Negeri Pahang/ Mohd Azuan Mohd Yusof - Mohd Yusof, Mohd Azuan (Universiti Teknologi MARA, Terengganu, 2010)
This study is about to investigate how do layout, ergonomics, and motivation can affect job productivity among employees at Pejabat MARA Negeri Pahang. There are several objectives of the study, first is to investigate the level of job productivity among employees at Pejabat MARA Negeri Pahang. Second is to identify the relationship between independent variables and dependent variable. Third is, to suggest some possible recommendations and suggestions to improve job productivity at Pejabat MARA Negeri Pahang. The dependent variable is job productivity. For the independent variable there are layout, ergonomics and motivation. Data collected was analyzed by using the Statistical Package for Social Science (SPSS). A sample of 36 staffs in Pejabat MARA Negeri Pahang, has completed questionnaire measures and reported their idea that lead to the determination to have better workspace layout, ergonomics, and motivation. In the chapter four will explain the finding analysis and interpretation in this study. This chapter comprises the testing normality, reliability analysis, frequency analysis, and means analysis. The research provides useful information on the employee’s determination towards better workspace layout, which of the area that needed to be rearranged or to be implementing some good layout planning and approaches. This research also provided the information about ergonomics and how to motivate the employee to increase their job productivity. / Mohd Azuan Mohd Yusof